Cost-effectiveness of bioimpedance-guided fluid management in patients undergoing haemodialysis: the BISTRO RCT - Mandana Zanganeh; John Belcher; James Fotheringham; David Coyle; Elizabeth J Lindley; David F Keane; Fergus J Caskey; Indranil Dasgupta; Andrew Davenport; Ken Farrington; Sandip Mitra; Paula Ormandy; et al. (Health Technology Assessment)
Background The BioImpedance Spectroscopy to maintain Renal Output randomised controlled trial investigated the effect of bioimpedance spectroscopy added to a standardised fluid management protocol on the risk of anuria and preservation of residual kidney function (primary trial outcomes) in incident haemodialysis patients. Despite the economic burden of kidney disease, the cost-effectiveness of using bioimpedance measurements to guide fluid management in haemodialysis is not known. Objectives To assess the cost-effectiveness of bioimpedance-guided fluid management against current fluid management without bioimpedance. Design Within-trial economic evaluation (cost–utility analysis) carried out alongside the open-label, multicentre BioImpedance Spectroscopy to maintain Renal Output randomised controlled trial. Setting Thirty-four United Kingdom outpatient haemodialysis centres, both main and satellite units, and their associated inpatient hospitals. Participants Four hundred and thirty-nine adult haemodialysis patients with > 500 ml urine/day or residual glomerular filtration rate > 3 ml/minute/1.73 m2. Intervention The study intervention was the incorporation of bioimpedance technology-derived information about body composition into the clinical assessment of fluid status in patients with residual kidney function undergoing haemodialysis. Bioimpedance measurements were used in conjunction with usual clinical judgement to set a target weight that would avoid excessive fluid depletion at the end of a dialysis session. Main outcome measures The primary outcome measure of the BioImpedance Spectroscopy to maintain Renal Output economic evaluation was incremental cost per additional quality-adjusted life-year gained over 24 months following randomisation. In the main (base-case) analysis, this was calculated from the perspective of the National Health Service and Personal Social Services. Sensitivity analyses explored the impact of different scenarios, sources of resource use data and value sets. Results The bioimpedance-guided fluid management group was associated with £382 lower average cost per patient (95% CI −£3319 to £2556) and 0.043 more quality-adjusted life-years (95% CI −0.019 to 0.105) compared with the current fluid management group, with neither values being statistically significant. The probability of bioimpedance-guided fluid management being cost-effective was 76% and 83% at commonly cited willingness-to-pay threshold of £20,000 and £30,000 per quality-adjusted life-year gained, respectively. The results remained robust to a series of sensitivity analyses. Limitations The missing data level was high for some resource use categories collected through case report forms, due to COVID-19 disruptions and a significant dropout rate in the informing BioImpedance Spectroscopy to maintain Renal Output trial. Conclusions Compared with current fluid management, bioimpedance-guided fluid management produced a marginal reduction in costs and a small improvement in quality-adjusted life-years. Results from both the base-case and sensitivity analyses suggested that use of bioimpedance is likely to be cost-effective. Future work Future work exploring the association between primary outcomes and longer-term survival would be useful. Should an important link be established, and relevant evidence becomes available, it would be informative to determine whether and how this might affect longer-term costs and benefits associated with bioimpedance-guided fluid management. Funding details This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number HTA 14/216/01 (NIHR136142). Plain language summary ‘Bioimpedance’ is a measure of how difficult it is for an electric current to pass through a biological object. Bioimpedance is used in devices that assess fluid status (over- or under-hydration) because it is very sensitive to the amount of water in tissue. Bioimpedance can be used in addition to clinical judgement when deciding how much water should be removed from someone with kidney failure during a dialysis treatment session. This is the first study to examine whether using this treatment represents a cost-effective use of National Health Service resources. We carried out an economic evaluation within a large randomised controlled trial in patients with kidney disease undergoing haemodialysis. We calculated the additional costs and quality-adjusted life-years (a measure that combines quality and quantity of life) using established methods. Over 2 years, our study showed that taking into account bioimpedance measurements about target weight resulted in slightly lower costs and marginally more quality-adjusted life-years, although there is uncertainty around these findings.